Financial Aspects of Private Pension Plans. - Dominiak, Gere; Philips, G. Edward (The Accounting Review, 1977)
Abstract Reviews the book "Financial Aspects of Private Pension Plans," by Mario Leo, Preston C. Bassett and Ernest S. Kachline.